Trade collapse during the covid-19 crisis and the role of demand composition - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
We examine the role of demand composition in explaining the trade collapse and recovery during the ongoing covid-19 crisis. We apply an import-intensity-adjusted measure of demand to examine import trends in 40 advanced and emerging economies over the period 1Q95 to 4Q20. We focus on the crisis periods related to covid-19 and the global financial crisis in 2008-2009. As during the global financial crisis, we find that import-intensity-adjusted demand is a key factor contributing to trade developments during the covid-19 crisis. The analysis also reveals substantial differences between the current crisis and the global financial crisis. Trade decline during the global financial crisis was heavily investment-led. In the current crisis, consumption and import demand from the service sector have had much larger roles. The recovery of trade has been notably faster during the covid-19 crisis and led by exports as opposed to the much more important role played by domestic demand during the global financial crisis.
URN:NBN:fi:bof-202109222030
Keywords: F10; F14; F17; G01; 330; International trade; covid-19; import-intensity-adjusted demand